2021
DOI: 10.1097/prs.0000000000009670
|View full text |Cite
|
Sign up to set email alerts
|

Aging, Skeletal Muscle, and Epigenetics

Abstract: Summary: We are living in an aging society. In 2019, 1 billion individuals were already aged over 60. The number of people in this demographic is predicted to reach 1.4 billion by 2030 and 2.1 billion by 2050 (WHO). In the USA, individuals over 65 represent the fastest growing segment of the population (US census bureau). Similar trends are seen in the UK, with 16.2 million people already aged over 60, equivalent to 24% of the total population (Age UK; https://www.ageuk.org.uk/globalassets/age-uk/d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 45 publications
0
3
0
Order By: Relevance
“…Interestingly, epigenetics enable the interaction between lifestyle/environmental factors and modifications to DNA and histones, without changes in the DNA sequence. These epigenetic "tags" occurring because of life course events can influence gene expression (Stewart and Sharples, 2022). Thus, our study demonstrated a significant difference in the methylation profile in genes of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Interestingly, epigenetics enable the interaction between lifestyle/environmental factors and modifications to DNA and histones, without changes in the DNA sequence. These epigenetic "tags" occurring because of life course events can influence gene expression (Stewart and Sharples, 2022). Thus, our study demonstrated a significant difference in the methylation profile in genes of the PI3K/Akt pathway.…”
Section: Discussionmentioning
confidence: 57%
“…Then we conducted MR analyses and found that overweight was significantly associated with TL decrease, FI increase and FA increase. TL decrease, FI increase and FA increase could be regarded as the signals of accelerated aging, for which the findings suggested that genetically predicted overweight might be causally related to accelerated aging (Cao et al, 2022;Chakravarti et al, 2021;Stewart & Sharples, 2022).…”
Section: Discussionmentioning
confidence: 98%
“…Then we conducted MR analyses and found that overweight was significantly associated with TL decrease, FI increase and FA increase. TL decrease, FI increase and FA increase could be regarded as the signals of accelerated aging, for which the findings suggested that genetically predicted overweight might be causally related to accelerated aging (Cao et al, 2022 ; Chakravarti et al, 2021 ; Stewart & Sharples, 2022 ). Moreover, the findings suggest that overweight was a risk factor for longevity expectancy, as indicated by the findings that overweight was causally associated with the decreased likelihoods of reaching/exceeding 90th survival percentile and 99th survival percentile, which was consistent with the previous clinical observations (Chen et al, 2019 ; Hensrud & Klein, 2006 ).…”
Section: Discussionmentioning
confidence: 99%